AL-IJARAH AL-MUNTAHIYAH BI AL-TAMLIK (IMBT) DALAM PERSPEKTIF ANATOMI KONTRAK BISNIS - Jaih Mubarok (Center for Research and Community Service of UIN Sultan Maulana Hasanuddin Banten-Serang City-Indonesia, 2009)
AI-Ijarah al-Muntahiyyah bi al-Tamlik (IMBT) is conceptually almost the same as leasing which is conducted by world financial institutions, including those of in Indonesia. IMBT is a service product of syari'a financial institution which is transparant and is able to involve the third party whenever it is necessary. In the context of Indonesia, economic syari'a is culturally designed and run by the Coumil of Indonesian Ulama (MUI). In order to regulate the bussiness in the syari'a system, MUI forms the Council of National Syari'a (DSN) issuing the fatwas; in order to give monitoring, DSN places The Board ef Syari'a Controller (DPS) in every business unit which uses syari'a system; in order to solve the syari'a business disputation, MUI forms the Arbitration Board of National Syari'a (Basyarnas). Moreover, The State has structurally accomodated the system of syari'a business in law and regulation. Therefore, The openess characteristics (the principle of free based contract) which is also practiced in the contract of IMBT is restricted by the law and regulation and considered appropriate in syari'a point of view based on DSN-MUI fatwas.